Critical Issues in the Management of Newborn Hearing Screening in the Time of COVID-19 in Umbria, Italy - Valeria Gambacorta; Eva Orzan; Egisto Molini; Ruggero Lapenna; Matteo Paniconi; Alfredo Di Giovanni; Mario Faralli; Giampietro Ricci (MDPI AG, 2022)
Hearing impairment is the most frequent of the sensorial defects in humans, and if not treated promptly, can severely impair cognitive and spoken language skills. For this reason, a universal newborn hearing screening (UNHS) has been established. The purpose of our study is to examine, by means of a retrospective analysis, the results of the UNHS program in the Umbria region during the spread of COVID-19 (2020-2021), comparing the same data from the years 2011-2012, to understand if the program has improved. Our study has shown how the coverage rate of well born babies' (WB) screening has significantly increased to currently meet the JCIH benchmark. The percentage of WB referrals significantly decreased in 2020-2021, another indicator of the screening program's greater efficiency in Umbria. However, a critical issue has emerged: the percentage of those lost to follow-up is greater than 30%, well above the benchmark. As far as the COVID-19 pandemic has certainly had a significant impact, it is necessary to carefully monitor those who do not access the diagnostic level. To emphasize the importance of a proper screening program, it will be helpful to strengthen the computerized data collection system and create an information network between audiologists, pediatricians and families.